Perilaku Hidup Bersih dan Sehat Masyarakat Lam Lagang Banda Aceh di Era New Normal - Fitrayandi, Rizki; Murni, Seri (Jurnal Riset dan Pengabdian Masyarakat, 2022)
The Covid-19 pandemic has changed many things in an instant. For this reason, a behavior change is needed to be clean and given a new normal era. In implementing the new normal, where the new normal state of the covid-19 virus is no longer there. A clean and healthy lifestyle is an effort to break the signs of the Covid-19 pandemic. The behavior of a clean and healthy life is one of the government's special concerns in implementing the new normal era. Attitudes, lifestyles, ways of working in the new normal era will not be the same as before the Covid-19. So they have to change their behavior, way of life, way of working and thinking in the new normal era. With the behavioral adaptations needed in the new normal era, they can be healthy have a long and productive life.